The need of a new management regarding the contradictory East-West European capital and labour flows. A regional welfare approach - Ionescu, Romeo Victor; Zlati, Monica Laura; Antohi, Valentin Marian (Technological and Economic Development of Economy, 2022)
The paper addresses an extremely current phenomenon: migration in opposite directions of FDI and labour, in context with the permanent need for economic growth and welfare. The analysis is carried out over a period of 12 years, in the context of setting objectives and working hypotheses regarding the realization of a correlation model of phenomena and optimization of migration flows in order to obtain welfare through economic development. The results of the research will reflect the relevance of the aggregation of the two migratory flows (FDI and labour) in order to obtain the financial leverage effect and the economic welfare in the analysed regions (EU, Germany and Romania).The conclusions of the study reflect the relevance of the method, the validity of the model and its relevance for the decision forums interested in the economic development and in increasing the population welfare.First published online 04 March 2022